Adherence to treatment: influence on life quality and risk of repeated fractures in women in post-menopause after osteoporotic fracture - O. V. Dobrovolskaya; N. V. Toroptsova (Лечащий Врач, 2021)
In cohort of women in menopause after osteoporotic fractures of different localizations, adherence to anti-osteoporotic treatment was studied, and its influence on changes in life quality and risk of new fractures in the course of 3-year follow-up period was evaluated. It was defined that adherence to the treatment during 3 years accounted for 20%. Life quality in those patients who got antiosteoporotic treatment, was recovered authentically faster, and the risk of repeated fractures in the patients who didn’t get the therapy, was 3,5 times higher.